Scientific Opinion on Flavouring Group Evaluation 06, Revision 3 (FGE.06Rev3): Straight‐ and branched‐chain aliphatic unsaturated primary alcohols, aldehydes, carboxylic acids, and esters from chemical groups 1 and 4 - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (Wiley, 2011)
Abstract The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to evaluate 50 flavouring substances in the Flavouring Group Evaluation 6, Revision 3, using the Procedure in Commission Regulation (EC) No 1565/2000. None of the substances were considered to have genotoxic potential. The substances were evaluated through a stepwise approach (the Procedure) that integrates information on structure‐activity relationships, intake from current uses, toxicological threshold of concern, and available data on metabolism and toxicity. The Panel concluded that the 50 substances [FL‐no: 02.125, 02.138, 02.152, 02.170, 02.175, 02.176, 02.195, 02.201, 02.222, 02.234, 05.061, 05.082, 05.143, 05.174, 05.203, 05.217, 05.218, 05.220, 05.226, 08.074, 08.100, 08.102, 09.341, 09.368, 09.377, 09.567, 09.569, 09.572, 09.575, 09.612, 09.638, 09.640, 09.643, 09.672, 09.673, 09.674, 09.831, 09.838, 09.884, 09.855, 09.871, 09.872, 09.885, 09.897, 09.898, 09.928, 09.937, 09.938, 09.939 and 09.950] do not give rise to safety concerns at their levels of dietary intake, estimated on the basis of the MSDI approach. Besides the safety assessment of these flavouring substances, the specifications for the materials of commerce have also been considered. For one substance [FL‐no: 09.938] an identity test is missing and for two substances [FL‐no: 05.226 and 09.950] the range of the specific gravity is too wide. Additional, the stereoisomeric mixture has not been specified sufficiently for 12 substances [FL‐no: 02.152, 02.222, 05.061, 05.203, 05.218, 08.074, 08.102, 09.377, 09.640, 09.831, 09.884 and 09.885].